UHF RFID reader antenna with high gain / Ismarani Ismail and S. M. Norzeli - Ismail, Ismarani; Norzeli, S. M. (UiTM Press, 2013)
An E-shaped microstrip single layer patch antenna with high gain is designed and analyzed for RFID (Radio Frequency Identification) reader applications. It has one port excited with microstrip line feed mechanism. To obtain an optimum peak gain, the effects of adding parasitic elements and slots are respectively investigated. The physical parameters of the novel structure as well as its partial ground plane are analyzed and optimized using commercial computer simulation technology (CST) simulation packages. Return loss (S11), voltage standing wave ratio (VSWR), directivity and gain are carried out. The results show that the proposed antenna has good impedance and radiation characteristics over the required bandwidth, 860-960 MHz (UHF RFID band). The return loss of the optimized E-shaped microstrip patch antenna is below 10dB over the UHF frequency band. The proposed antenna is very promising for various modern communication applications.